The Influence IT Governance Mechanism on Effectiveness ITG and IT Performance: A Partial Least Squares Structural Equation Modeling Approach (PLS-SEM) - Anwar Fattah; Hoga Saragih; Titik Khawa Abdul Rahman; Resad Setyadi (International Journal of Science, Technology & Management, 2021)
This article presents raw inferential statistical data that determine the IT Governance effectiveness on the IT Performance.To identify influence mechanism Information Technology Governance (ITG) on Effectiveness ITG and IT Performance.Data were collected from respondents in all regions of Indonesia. Quantitative research methods are used to analyze data. The structured questionnaire was distributed to respondents in all regions of Indonesia who understood the field of IT Governance in Higher University whose reliability and validity were confirmed. Structural equation modeling (SEM) using Smart PLS software, version 3, is used to present data. SEM path analysis shows an estimate of the relationship of the main constructs in the data The results obtained from this dataset shows positive relationship between mechanism Structure, Process and Relation to IT Governance effectiveness, consciousness also has a significant influence on the IT Performance and positive relationship between IT Governance effectiveness and IT Performance. However, mechanism structure and process has proven to have a negative and insignificant influence on the IT Performance Effective IT governance related to mechanism ITG and IT Performance level of unit analysis. One of the more significant findings to emerge from this study is that evaluate the mechanism ITG impact to effective IT governance that focus on higher education institution (HEI). This study already examines a validation of evaluation model and collecting data in particular higher education institution (HEI) as a single case study.